Pembuatan Alat Incinerator Limbah Padat Medis Skala Kecil - Sukamta Sukamta; Andri Winata; Thoharuddin Thoharuddin (Semesta Teknika, 2017)
Trash is one of the major problems in big cities. Trash has negative impact on the environment, because waste can cause environmental pollution, as well as hygiene and health problems. For processing the solid medical waste, it must be combusted at temperatures higher than 800 °C to reduce combustible garbage that can no longer be recycled, and toxic chemicals, to kill bacteria and virus. In energy efficient perspective, to overcome this, an incinerator has been developed. The main incenartor frame is made of iron elbow. The iron elbow is cut using an appropriate machine depending on the dimension of the design, and they are assembled by welding process. The furthure step is to complete by manufacturing of the chamber, and chimneys. The wall of he incinerator machine is made of red bricks, and glass woll for insulators. To measure and control the temperature, thermocuple and thermocontrol being put on the inner wall of the incinerator machine are used. The function of the incinerator machine was tested, and it wotked well. Commisioning test of the machine for solid medical waste i.e. infusion bottles, spets, glass bottles, baby pempers and expired medicines were conducted. It shows that the acheived temperature is of 998⁰C during 25 minutes of the opearation and all of the solid waste have become ash except needle, plastic and glass. So, this machine can be operated as a small scale solid medical waste processing equipment.